Clinical Outcomes of Implant-Supported Prostheses versus Conventional Dentures in Edentulous Patients - Buston ugli, Islomov Lazizbek; Javokhirkhon Davron, Buzrukzoda (American Journal of Biomedicine and Pharmacy, 2026)
Edentulism remains a major oral health problem worldwide, significantly affecting mastication, speech, facial aesthetics, and overall quality of life. Conventional complete dentures have long been the standard treatment for edentulous patients; however, limitations such as poor retention, instability, and progressive alveolar bone resorption often compromise functional and patient-reported outcomes. Implant-supported prostheses have emerged as an effective alternative, offering enhanced stability, improved chewing efficiency, and greater patient satisfaction. This article provides a comprehensive comparative analysis of clinical outcomes associated with implant-supported prostheses and conventional complete dentures in edentulous patients. Functional performance, biological and mechanical complications, patient satisfaction, quality of life, and long-term success are critically evaluated to determine optimal treatment strategies in contemporary prosthodontic practice. This article presents a comprehensive analytical synthesis of clinical outcomes associated with implant-supported prostheses in comparison with conventional complete dentures among edentulous patients. Emphasis is placed on functional efficiency, patient-centered outcomes, long-term stability, biological responses, and complication profiles. By integrating evidence from contemporary clinical studies, the work highlights how implant-based rehabilitation addresses key limitations of traditional removable dentures, including reduced masticatory performance, progressive alveolar bone resorption, and compromised quality of life. The analysis underscores the evolving role of implant-supported solutions as a standard of care in modern prosthodontics while acknowledging economic, anatomical, and systemic factors that influence treatment selection.